Some urinary excretion of steroids in the native coast and in the high and the coastal changes experienced in adapting to the height - San Martín, M. (1954)
The coastal and native resident of the height 4,560 meters, statistically no different in the excretion of 17 ketosteroids and neutral reducing the steroids. The coastal within the first 12 months of its adaptation to high altitude, showing changes in the urinary excretion of these steroids.